Penyuluhan Hukum tentang Pencegahan Tindak Pidana Korupsi di Tingkat Desa - Bruri Marwano Wutwensa; Dwi Andika (UPPM STIH Biak-Papua, 2024)
Transparent and accountable management of Village Funds is an important aspect in supporting sustainable village development and improving community welfare. This community service aims to provide understanding to village officials, and the community in managing village funds. This service uses a participatory approach method through seminars, interactive discussions, and legal counseling. The results of this service show that there is an increase in participants' understanding of the importance of good Village Fund management in accordance with applicable regulations, such as Law Number 6 of 2014 concerning Villages and Law Number 31 of 1999 concerning the Eradication of Corruption. In addition, this activity also succeeded in building participants' awareness of the strategic role of the community in supervising the management of Village Funds to prevent corrupt practices.